Subintimal Ki-67 as a synovial tissue biomarker for inflammatory arthropathies. Issue 2 (5th July 2007) - Pessler, F; Ogdie, A; Diaz-Torne, C; Dai, L; Yu, X; Einhorn, E; Gay, S; Schumacher, H R
Abstract : Objectives: Ki-67 is expressed in the nuclei of dividing cells and can be used to assess proliferation of synovial inflammatory and stromal cells. We evaluated subintimal Ki-67+ cell density as a tissue biomarker for inflammatory arthropathies and compared it to subintimal CD68, a synovial biomarker of RA. Methods: Subintimal Ki-67+ and CD68+ cell densities were measured immunohistochemically in synovial specimens obtained from patients with rheumatoid arthritis (RA; n = 19), osteoarthritis (OA; n = 18), "non-inflammatory" orthopaedic arthropathies (avascular necrosis, meniscus injury, femur fracture; n = 16), chronic septic arthritis (n = 9), and histologically normal synovium (n = 10). Results were correlated with a histological synovitis score. Utilising the areas under receiver operating characteristic curves (AUCs), we compared the abilities of Ki-67 and CD68 to differentiate among these arthropathies. Results: Ki-67 was expressed widely in the subintima of inflamed specimens and in RA pannus invading hard tissues. Compared to normal controls, it was highly overexpressed in RA (26.6-fold) and chronic septic arthritis (55-fold), and mildly elevated in OA (3.9-fold) and orthopaedic arthropathies (2.1-fold). Ki-67 and CD68 differentiated similarly well between RA and OA (AUC: Ki-67 = 0.91, CD68 = 0.94), Ki-67 better between chronic septic arthritis and RA, and CD68 better between OA and normal controls. Ki-67 ( r  = 0.80) and CD68 ( r  = 0.79) correlated positively with the synovitis score. Conclusions: Subintimal Ki-67 was overexpressed in inflammatory arthropathies, distinguished among differentially inflamed arthropathies, and correlated positively with the histological severity of synovitis. It may prove useful in synovial tissue classification and as a synovial marker of disease activity in clinical trials when biopsies are available.